Optimalisasi Strategi Penangkapan Pole and Line melalui Variasi Jenis Umpan dan Waktu Tangkap sebagai Instrumen Industrialisasi Bahari Berkelanjutan di Jepang - Perdana Ixbal Spanton; Prayogo, Luhur Moekti; Jumiati; Achmad Sudianto; Nova Widiantoro (Pena Akuatika : Jurnal Ilmiah Perikanan dan Kelautan, 2025)
As a country with a very high level of fish consumption, Japan relies heavily on the marine sector, especially in the activity of catching abundant marine products. Various types of fishing gear have been developed, ranging from traditional equipment to modern technology using machines and robots. These efforts are made by the Japanese government to ensure the availability of fresh fish for its people. This study aims to compare fish catches based on different colors of artificial bait and to identify and analyze the effect of bait color on the effectiveness of catches directly in the field. The research material focuses on the comparison of artificial bait colors to improve the catch of the pole and line method. The method used in this research is descriptive qualitative. The results showed that silver-colored bait was most effective in attracting skipjack, with the highest number of catches compared to the other two bait colors. In addition, catches were recorded significantly higher in the morning session (07:00-11:00) compared to the afternoon and evening sessions. The fishing location factor also contributed to the variation in catch, with some locations showing higher levels of productivity. These findings confirm the importance of choosing the right time, location and bait color to optimize catch using the pole and line method.